2015
DOI: 10.1017/edp.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

The Role of School Counsellors and Psychologists in Supporting Transgender People

Abstract: As growing numbers of transgender people -including students, parents, and educators -become visible within schools, so comes with this the requirement that schools ensure their full inclusion. This article suggests that school counsellors and psychologists have an important role to play in supporting transgender people within schools. As an initial scoping of this suggestion, the article reports on findings from two Australian surveys: one focused on cisgender parents of transgender children, and one focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…However, the findings suggest that women had more positive attitudes when compared with men. This echoes findings reported in previous research on the attitudes of school staff (Riggs & Bartholomaeus, 2015;Bowers et al, 2015;Silveira & Goff, 2016), psychologists and psychology students (Riggs & Sion, 2016), and the general population (e.g. Nagoshi et al, 2008;Norton and Herek, 2013) towards trans and gender diverse people, in which men have been found to have a greater investment in, and anxiety about, the gender order and their place in it, which it has been suggested leads to more transphobic attitudes and behaviours (Riggs & Sion, 2016;Nagoshi et al, 2008;Norton and Herek, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the findings suggest that women had more positive attitudes when compared with men. This echoes findings reported in previous research on the attitudes of school staff (Riggs & Bartholomaeus, 2015;Bowers et al, 2015;Silveira & Goff, 2016), psychologists and psychology students (Riggs & Sion, 2016), and the general population (e.g. Nagoshi et al, 2008;Norton and Herek, 2013) towards trans and gender diverse people, in which men have been found to have a greater investment in, and anxiety about, the gender order and their place in it, which it has been suggested leads to more transphobic attitudes and behaviours (Riggs & Sion, 2016;Nagoshi et al, 2008;Norton and Herek, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Research with parents of young trans and gender diverse children suggests that a key barrier to inclusion relates to school staff members' understandings of gender, and whether discussions of gender diversity are viewed as taboo or are positively included within school policies and practices (Pullen Sansfaçon, et al, 2015). Studies show that a lack of knowledge amongst staff makes school experiences difficult for both parents and children (Riggs & Bartholomaeus, 2015;Pullen Sansfaçon, et al, 2015), and that parents may even experience hostility from staff (Riggs & Bartholomaeus, 2015;Kuvalanka, et al, 2014). Other studies have found that parents fear for their child's safety at school (Hill & Menvielle, 2009;Riley, Sitharthan, Clemson, & Diamond, 2013).…”
Section: Trans and Gender Diverse Students' And Their Parents' Experimentioning
confidence: 99%
“…Walch et al's ( 2012 ) ATTI consists of 20 items derived primarily from existing homophobia scales, all of which loaded on one factor with a reliability of α = 0.95. While Walch et al ( 2012 ) demonstrated discriminant and convergent validity and Riggs and Bartholomaeus ( 2015 ) demonstrated the predictive validity of the ATTI, Riggs and Bartholomaeus's ( 2016 ) application of the ATTI to an independent sample produced no statistically significant results. They hypothesized that may have been because the ATTI, “despite the amendments made, is relatively blunt” (Riggs and Bartholomaeus, 2016 , p. 216).…”
Section: Introductionmentioning
confidence: 99%
“…Across the world, trans people (referring here, following Riggs & Bartholomaeus, 2015, to people whose gender differs from that normatively expected of their assigned sex) are increasingly accessing mental health services. Yet previous research suggests that many trans people have negative experiences with mental health care providers (e.g., del Pozo de Bolger, Jones, Dunstan, & Lykins, 2014;Ellis, Bailey, & MacNeil, 2015; McNeil, Bailey, Ellis, Morton, & Regan, 2012;Riggs, Coleman, & Due, 2014).…”
Section: Introductionmentioning
confidence: 99%